Review of experience of major reform of railways of the world - Martsenyuk, L. V. (Science and Transport Progress, 2013)
Purpose. To evaluate the possibility of the foreign countries experience in the reforming of railway transport of Ukraine. Methodology. On the basis of comparative analysis the suitability of foreign experience of infrastructure branches reformation, dividing the range of problems to the questions of ideological and methodological character, and of course, taking into account the peculiarities of the situation in Ukraine is estimated. As for the first range of problems, it is, first of all, the choice of the form of ownership. Findings. Experience shows that both types of property have not only the beneficial but also the negative impacts. On the one hand, it is the state railways have the conditions for development and implementation of the new technologies such as high-speed trains, construction of which, as well as construction of specialized lines would be impossible without appropriate research base, and without public funding. On the other – private companies. operating on a concession basis, usually provide a higher level of services at affordable rates. Originality. It can be concluded that there is no direct correlation between the ownership form of railroads and economic or qualitative characteristics of their work. The necessity of various forms of technical and economic relationships, the existence of separate railways at the regional and local levels, which offers a great opportunity to overcome the monotony of operation, in the development of railways towards greater differentiation of service levels is proved. This however does not mean that the only alternative is to sell concessions to private enterprises, especially if the transfer of ownership is not supplemented by commitments to support public transport at a certain level. Practical value. Examples of positive governance are opposed to the equal examples of private management and vice versa. Deep analysis of reforming experience of world leading railways will prevent from mistakes during "UZ" reforming.